Noble metal and Mn3O4 supported carbon nanotubes: Enhanced catalysts for ethanol electrooxidation - Suwaphid Themsirimongko (2018)
The carbon nanotubes (CNT) were modified by Mn3O4 before deposition of metal catalysts (e.g. Pt and Pd) by improved polyol method. Crystallinity, morphology and composition of the synthesized electrocatalysts were characterized by Fourier transform infrared (FT-IR) spectroscopy, x-ray diffraction (XRD), transmission electron microscopy (TEM) and energy dispersive x-ray spectroscopy (EDS). It was found that the Mn3O4 nanoparticles are dispersed and covered the CNT surface. The various atomic ratios of 10 wt% PtxPdy nanoparticles are also uniformly dispersed on Mn3O4-CNT with the particle size of 1-4 nm. Their electrocatalytic performances in ethanol oxidation were investigated by cyclic voltammetry (CV) and Chronoamperometry (CA). The prepared catalyst showed enhanced catalytic activity and more stability than the commercially available PtRu/Vulcan XC-72 catalyst. It is proposed that additions of metal oxides and noble metal could develop active sites for ethanol oxidation, which their catalytic performances were improved. These results imply that the prepared various atomic ratios PtxPdy/Mn3O4-CNT nanocomposite could be a promising electrocatalyst to enhance performance of direct ethanol fuel cell applications.